Electrophoretic separation of neurotransmitters on a polystyrene nano-sphere∕polystyrene sulphonate coated poly(dimethylsiloxane) microchannel - Zhao, Jinjin (American Institute of Physics, 2011)
In this paper, a poly(dimethylsiloxane) microchip with amperometric detector was developed for the electrophoretic separation and determination of neurotransmitters. For increasing the separation efficiency, the microchannel is modified by polystyrene sulphonate∕polystyrene nano-sphere self-assembly coating. A stable electro-osmotic flow (EOF) and higher separation efficiency are obtained in proposed modified microchannel. Under optimized conditions, dopamine, epinephrine, catechol, and serotonin are acceptably baseline separated in this 3.5 cm length separation channel with the theoretical plate number from 4.6 × 10(4) to 2.1 × 10(5) per meter and resolution from 1.29 to 12.5. The practicability of proposed microchip is validated by the recovery test with cerebrospinal fluid as real sample which resulted from 91.7% to 106.5%.